Dynamic Signatures of the Epigenome: Friend or Foe? - Marta Machnik; Urszula Oleksiewicz (Cells, 2020)
Highly dynamic epigenetic signaling is influenced mainly by (micro)environmental stimuli and genetic factors. The exact mechanisms affecting particular epigenomic patterns differ dependently on the context. In the current review, we focus on the causes and effects of the dynamic signatures of the human epigenome as evaluated with the high-throughput profiling data and single-gene approaches. We will discuss three different aspects of phenotypic outcomes occurring as a consequence of epigenetics interplaying with genotype and environment. The first issue is related to the cases of environmental impacts on epigenetic profile, and its adverse and advantageous effects related to human health and evolutionary adaptation. The next topic will present a model of the interwoven co-evolution of genetic and epigenetic patterns exemplified with transposable elements (TEs) and their epigenetic repressors Krüppel-associated box zinc finger proteins (KRAB−ZNFs). The third aspect concentrates on the mitosis-based microevolution that takes place during carcinogenesis, leading to clonal diversity and expansion of tumor cells. The whole picture of epigenome plasticity and its role in distinct biological processes is still incomplete. However, accumulating data define epigenomic dynamics as an essential co-factor driving adaptation at the cellular and inter-species levels with a benefit or disadvantage to the host.